2015
DOI: 10.1002/cne.23736
|View full text |Cite
|
Sign up to set email alerts
|

Topographic organization and possible function of the posterior optic tubercles in the brain of the desert locust Schistocerca gregaria

Abstract: Migrating desert locusts, Schistocerca gregaria, are able to use the skylight polarization pattern for navigation. They detect polarized light with a specialized dorsal rim area in their compound eye. After multistage processing, polarization signals are transferred to the central complex, a midline-spanning brain area involved in locomotor control. Polarization-sensitive tangential neurons (TB-neurons) of the protocerebral bridge, a part of the central complex, give rise to a topographic arrangement of prefer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 25 publications
(48 citation statements)
references
References 62 publications
1
47
0
Order By: Relevance
“…This neuroarchitecture is paralleled by a neurochemical architecture as revealed, for example, in the axonal projections of subsets of neurons from the PI expressing serotonin (5HT) and allatostatin (AST) in the adult (Figure 5A), or by diaphorase (NADPHd) staining as a marker for nitric oxide (NO) already at 85% of embryogenesis (Figures 5Bi,ii). This congruence of anatomical and neurochemical architecture can also be demonstrated using a range of other molecules (Homberg, 2002; Herbert et al, 2010; Pfeiffer and Homberg, 2014; Beetz et al, 2015) whose contributions to adult behaviors are steadily being revealed (Seidel and Bicker, 1996, 2002; Homberg, 2002; Nässel, 2002; Winther et al, 2006; Kahsai and Winther, 2011; Kunst et al, 2011). The question at the center of this study is when and how these stereotypic neurochemical projection patterns arise during embrygenesis.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…This neuroarchitecture is paralleled by a neurochemical architecture as revealed, for example, in the axonal projections of subsets of neurons from the PI expressing serotonin (5HT) and allatostatin (AST) in the adult (Figure 5A), or by diaphorase (NADPHd) staining as a marker for nitric oxide (NO) already at 85% of embryogenesis (Figures 5Bi,ii). This congruence of anatomical and neurochemical architecture can also be demonstrated using a range of other molecules (Homberg, 2002; Herbert et al, 2010; Pfeiffer and Homberg, 2014; Beetz et al, 2015) whose contributions to adult behaviors are steadily being revealed (Seidel and Bicker, 1996, 2002; Homberg, 2002; Nässel, 2002; Winther et al, 2006; Kahsai and Winther, 2011; Kunst et al, 2011). The question at the center of this study is when and how these stereotypic neurochemical projection patterns arise during embrygenesis.…”
Section: Discussionmentioning
confidence: 82%
“…Since most of the substances examined here are expressed in subsets of tangential and columnar neurons, and some additionally in pontine neurons, our current level of resolution does not allow us to relate a given temporal expression pattern to the functional morphology of individual neuron types. This may eventually prove possible for certain columnar (CPU1, 2) or tangential (TB1a, TB1d) neurons with regionalized morphologies spanning different modules (see Heinze and Homberg, 2008; Pfeiffer and Homberg, 2014; Beetz et al, 2015) if these neurons were to also regionalize their developmental expression of a given neurochemical.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These neurons gave rise to immunostaining in particular layers of the medulla. In S. gregaria , Homberg, Brandl, Clynen, Schoofs, & Veenstra () and Beetz, el Jundi, Heinze, and Homberg () have distinguished 10 layers, numbered 1–10 from distal to proximal. GABA immunostaining was particularly dense in layers 4, 8, 9, and 10, and had a columnar appearance in distal layers 1‐3 (Figure b,e).…”
Section: Resultsmentioning
confidence: 99%
“…To prevent this excitation to spread across the entire circuit, lateral inhibition is required [9496,100]. Whereas direct evidence for the cell-type providing this inhibition is lacking, local interneurons of the PB (closely resembling TB1 neurons from other insects [92,101]) appear to be the most promising candidates [100]. These cells have complex branching patterns [84,102] covering the entire PB and could connect all E-PG cells to one another in ways compatible with ring attractor circuits.…”
Section: The Neural Basis Of Path Integrationmentioning
confidence: 99%